2015
DOI: 10.1007/s00259-015-3094-6
|View full text |Cite
|
Sign up to set email alerts
|

Test–retest reproducibility of the metabotropic glutamate receptor 5 ligand [18F]FPEB with bolus plus constant infusion in humans

Abstract: Purpose [18F]FPEB is a promising PET radioligand for the metabotropic glutamate receptor 5 (mGluR5), a potential target for the treatment of neuropsychiatric diseases. The purpose of this study was to evaluate the test-retest reproducibility of [18F]FPEB in the human brain. Methods Seven healthy male subjects were scanned twice, 3–11 weeks apart. Dynamic data were acquired using bolus plus infusion of 162±32 MBq [18F]FPEB. Four methods were used to estimate volume of distribution (VT): equilibrium analysis (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
59
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(62 citation statements)
references
References 28 publications
3
59
0
Order By: Relevance
“…Based on previous studies showing that equilibrium was reached at 60 min, emission data were acquired 90-120 min after the start of injection on the high-resolution research tomograph (Siemens/CTI), which has intrinsic spatial resolution of ∼2.5 mm FWHM. We have previously shown that venous and arterial concentrations are wellmatched at equilibrium, allowing venous sampling to be collected for metabolite correction as opposed to the more invasive arterial sampling (19). We also showed good test-retest variability (mean TRV of 12%) of […”
Section: Methodsmentioning
confidence: 66%
See 4 more Smart Citations
“…Based on previous studies showing that equilibrium was reached at 60 min, emission data were acquired 90-120 min after the start of injection on the high-resolution research tomograph (Siemens/CTI), which has intrinsic spatial resolution of ∼2.5 mm FWHM. We have previously shown that venous and arterial concentrations are wellmatched at equilibrium, allowing venous sampling to be collected for metabolite correction as opposed to the more invasive arterial sampling (19). We also showed good test-retest variability (mean TRV of 12%) of […”
Section: Methodsmentioning
confidence: 66%
“…[ 18 F]FPEB was administered i.v. as bolus plus infusion for 120 min, with a K bol of 190 min (19,76). Based on previous studies showing that equilibrium was reached at 60 min, emission data were acquired 90-120 min after the start of injection on the high-resolution research tomograph (Siemens/CTI), which has intrinsic spatial resolution of ∼2.5 mm FWHM.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations